Developing Fixher Using Scrum Model - Hendi Sama; Darvin Darvin (Journal of Information System and Technology (JOINT), 2021)
The automotive industry in Indonesia has suggestively increased during the past several years, thus drives people with the desire to own private transportations, in which positively correlates to generate huge markets in repairing and maintenance works. Meanwhile, lots of automobile owners have troubles in selecting workshop due to their either lack of available workshops’ information or even due to services being provided by workshops. The goal of FiXHER is solving the problems stated. By providing detail information to their very door step in application mobile platform, is believe to be able to minimize breakdown and improve productivity for both automobile owners and workshops. With the help of agile methodology, scrum model, FiXHER mobile application is maintained in its best way and finished before estimate times.